L1 Usage in English Teaching: Students’ Perspective - Asriati Asriati; Baso Jabu (Universitas Cokroaminoto Palopo, 2022)
This study aims to explore the usage of L1 in teaching English based on the students’ perspectives. The study employed questionnaire and interview to obtain the data about the students’ perspectives on the usage of L1 in EFL classroom, the proper contexts where the lecturer must use L1, and whether there are differences from the low and high achiever students’ perspectives. There are 163 participants from English education students contribute to this study and 37 of them are interviewed. The results suggest that the students have positive attitude toward the using of Bahasa Indonesia as the students first language (L1) in their English classroom, particularly when the lecturers explaining difficult linguistic concept and clarifying their instructions. There is no different opinion between the low and high achiever students toward the using of L1 in the teaching and learning process. They all agree that Bahasa Indonesia as the students’ first language still holds an important role in the process of learning foreign languages.